Scales of Online Learning Readiness: Empirical Validation of Factors Affecting EFL Learners in Online Learning during Covid-19 Pandemic - Ni Wayan Surya Mahayanti; Nur Hidayanto Pancoro Setyo Putro; Pratomo Widodo; Dennis Alonzo (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
Although extensive research has been carried out on university students’ online learning readiness, very little attention has been paid to online learning readiness of foreign language learners. Examining the learners' readiness get involved in online learning becomes more fundamental to conduct in this current Covid-19 pandemic since online learning is the only alternative to run educational programs at every level. This study set out to investigate the construct validity of a scale to measure EFL learners' readiness in online learning during covid-19 pandemic. The scale was construdted based on the theories underlying students readiness in online learning. Both exploratory and confirmatory factor analyses were used to empirically validate the scale. A total of 682 undergraduate students from seven universities in Indonesia participated in the study by completing in the google form-based scale. The results of the study showed that the scale comprised of 24 items that converged into a five-latent factor with an acceptable fit. These results are expected to be a consideration basis in planning, implementing, and evaluating EFL online learning programs in the Indonesia context.